The Mediumship of Carlos Mirabelli (1889-1951) - Braude, Stephen (Journal of Scientific Exploration, 2017)
The case of the Brazilian medium, Carlos Mirabelli, is one of the most tantalizing and frustrating in psychical research. If his phenomena—especially his psychokinetic manifestations—occurred as reported, he was probably the greatest physical medium of all time. Mirabelli reportedly moved objects (including very large objects) at a distance, levitated himself while bound to a chair, and dematerialized and transported to another location objects of all kinds (including himself). Mirabelli also reportedly produced full-figure materializations in bright daylight. Sitters would watch them form; attending physicians would carefully examine them for up to 30 minutes and report ordinary bodily functions; photographs of the figures would be taken; and then they would slowly dissolve or fade before everyone’s eyes. However, Mirabelli was also clearly guilty of fraud on occasion, including his notorious doctoring of a photo ostensibly showing him to be levitating. His case therefore presents an all too familiar challenge to psi research—namely, how to assess cases of so-called “mixed” mediumship.